EVALUATION OF SILICA-WATER SURFACE CHEMISTRY USING NMR SPECTROSCOPY - Carroll S.A.; Maxwell R.S.; Bourcier W.; Martin S.; Hulsey S. (My University, 2002)
We have combined traditional batch and flow-through dissolution experiments, multinuclear nuclear magnetic resonance (NMR) spectroscopy, and surface complexation modeling to re-evaluate amorphous silica reactivity as a function of solution pH and reaction affinity in NaCl and CsCl solutions. The NMR data suggest that changes in surface speciation are driven by solution pH and to a lesser extent alkali concentrations, and not by reaction time or saturation state. The 29Si cross-polarization NMR results show that the concentration of silanol surface complexes decreases with increasing pH, suggesting that silanol sites polymerize to form siloxane bonds with increasing pH. Increases in silica surface charge are offset by sorption of alkali cations to ionized sites with increasing pH. It is the increase in these ionized sites that appears to control silica polymorph dissolution rates as a function of pH. The 23Na and 133Cs NMR results show that the alkali cations form outersphere surface complexes and that the concentration of these complexes increases with increasing pH. Changes in surface chemistry cannot explain decreases in dissolution rates as amorphous silica saturation is approached. We find no evidence for repolymerization of the silanol surface complexes to siloxane complexes at longer reaction times and constant pH.